Comparison of vulnerabilities in typical bridges using macroseismic intensity scales. (June 2022) - Li, Si-Qi; Liu, Hong-Bo
Abstract: The macroseismic intensity scale in different regions is extensively assessed in the vulnerability assessment of building structures and is rarely used to quantify the damage characteristics of group bridges. To more accurately examine the differences in the seismic vulnerability of typical bridges in an earthquake-damaged region under multiple intensity scales, this study analyses the vulnerability of 1516 girder bridges and 612 arch bridges affected by the Wenchuan earthquake, which occurred on May 12, 2008, in China, by using the European Macroseismic scale, Medvedev, Sponheuer, and Karnik scale, and the Chinese Seismic Intensity scale based on the principle of nonlinear regression and probability models. The vulnerability matrices, functions, and curves of the update models to compare girder bridges and arch bridges were obtained based on the number of samples and their failure ratio. When combined with the new cumulative exceeding probability model, curves of the exceeding probability model of girder bridges and arch bridges under the different intensity scales were obtained and compared. A parameter matrix model is proposed to evaluate and predict the seismic vulnerability of regional bridges. Combined with empirical data on the seismic damage caused to the girder bridges and arch bridges in the earthquake, their vulnerability matrices, curves, and point cloud models were obtained under a multi-intensity scale of assessment for a comparative analysis. The conclusions of this study can be used for an accurate assessment of the vulnerability of typical bridges in the future.